Prospective Cohort Study Investigating the Safety and Efficacy of Ambulatory Treatment With Oral Cefuroxime-Axetil in Febrile Children With Urinary Tract Infection - Hennaut, Elise; Duong, Hong P.; Chiodini, Benedetta; Adams, Brigitte; Lolin, Ksenija; Blumental, Sophie; Wissing, Karl M.; Ismaili, Khalid (Frontiers in Pediatrics, 2018)
Aims: to assess the safety and efficacy of ambulatory oral cefuroxime-axetil treatment in children presenting with first febrile urinary tract infection (UTI) in terms of resolution of fever, antibiotics tolerance, bacterial resistance, and loss to ambulatory follow-up. Methods: Two-year prospective single-center evaluation of the local protocol of oral ambulatory treatment of children presenting first febrile urinary tract infection (UTI). Results: From October 2013 to October 2015, 82 children were treated ambulatory with oral cefuroxime-axetil. The median age was 8 months. When analyzing those 82 children treated orally, 51 (62%) completed oral treatment, 14 (17%) were not returned for their scheduled follow-up visits (3 patients at day 2 and 11 patients at week 2), and 17 (21%) were switched to IV therapy for the following reasons: vomiting in 9, persistent fever in 5, antibiotic resistance in 2 and bacteremia in 1. Six children (8%) presented recurrent UTI after a median of 5 months of follow-up. Conclusions: This 2-year evaluation suggests that oral treatment with cefuroxime-axetil in febrile UTI is feasible but should be implemented with caution. Home-treated children require reevaluation during treatment since 21% of our cohort had to be temporarily switched to parenteral therapy and 17% did not attend follow up visits during oral treatment.